The Influence of Social Media on Youth Political Engagement in the 2024 Elections - Hisbul Wathan; Yusrijal Masri (Generasi Sains Indonesia, 2024)
This is because the present study will seek to explore the role of digital interaction on youth engagement through political involvement in the 2024 elections thereby isolating a gap within the literature of political action and digital interaction. Using a quantitative research method conducted online, the information was collected as a structured survey among the population of young voters aged between 18-30. The research came up with a positive correlation between the duration of use of social media with political participation, a coefficient of 0.45, and between exposure to political contents and political participation of 0.52. In addition, the engagement level was also found to be enhanced by increasing the frequency of discussing politics over the web (r = 0.35). These facts further bring out the significance role of social media as a major platform of discussions and organization of political activities and events particularly among youths who are increasingly using products of the social media to share information and perform interactions. Based on the study, the knowledge of the way through which social media affects political perceptions and actions in highly polarized electoral settings can be proceeded with. Among these is the consideration of the future research on the nature of technological based activism in the electoral process that would empower the youth political enlightenment of the voting population. Such findings are crucial to the theoretical and practice aspects of the previous government, schools, and political parties in the capacity to understand the youths and organize young citizens to mobilize them.